Deaths from acute abdominal conditions and geographical access to surgical care in India: a nationally representative spatial analysis. Issue 10 (October 2015) - Dare, Anna J; Ng-Kamstra, Joshua S; Patra, Jayadeep; Fu, Sze Hang; Rodriguez, Peter S; Hsiao, Marvin; Jotkar, Raju M; Thakur, J S; Sheth, Jay; Jha, Prabhat; ,
Summary: Background: Few population-based studies quantify mortality from surgical conditions and relate mortality to access to surgical care in low-income and middle-income countries. Methods: We linked deaths from acute abdominal conditions within a nationally representative, population-based mortality survey of 1·1 million households in India to nationally representative facility data. We calculated total and age-standardised death rates for acute abdominal conditions. Using 4064 postal codes, we undertook a spatial clustering analysis to compare geographical access to well-resourced government district hospitals (24 h surgical and anaesthesia services, blood bank, critical care beds, basic laboratory, and radiology) in high-mortality or low-mortality clusters from acute abdominal conditions. Findings: 923 (1·1%) of 86 806 study deaths at ages 0–69 years were identified as deaths from acute abdominal conditions, corresponding to 72 000 deaths nationally in 2010 in India. Most deaths occurred at home (71%) and in rural areas (87%). Compared with 567 low-mortality geographical clusters, the 393 high-mortality clusters had a nine times higher age-standardised acute abdominal mortality rate and significantly greater distance to a well-resourced hospital. The odds ratio (OR) of being a high-mortality cluster was 4·4 (99% CI 3·2–6·0) for living 50 km or more from well-resourced district hospitals (rising to an OR of 16·1 [95% CI 7·9–32·8] for >100 km). No such relation was seen for deaths from non-acute surgical conditions (ie, oral, breast, and uterine cancer). Interpretation: Improvements in human and physical resources at existing government hospitals are needed to reduce deaths from acute abdominal conditions in India. Full access to well-resourced hospitals within 50 km by all of India's population could have avoided about 50 000 deaths from acute abdominal conditions, and probably more from other emergency surgical conditions. Funding: Bill & Melinda Gates Foundation, Dalla Lana School of Public Health, Canadian Institute of Health Research .